Prótesis para caninos con amputaciones totales (2020)
Animals, like humans, suffer from either congenital or acquired diseases that often affect their limbs. The most common way in which these are treated is by means of the partial or total amputation of the limb. However, the consequences of this type of surgical solution not only reduce the freedom of movement of these animals, but also have negative repercussions on their health. On the other hand, there is also the fact that despite the fact that there has been an increase in the acceptance and establishment of a more ethical treatment for animals, especially for companion animals such as cats and dogs, it has not been seen great interest on the part of the market in finding a solution for those animals that have seen their mobility reduced. As a result of this lack of interest, there are few prosthetics on the market for animals, most of which are custom made, making them extremely expensive and difficult to acquire for the average household. For this reason, we want to find a way to facilitate movement in canines with total amputations to provide a better experience for the patient and caregivers, where their adaptability to everyday environments is ensured.